1995
DOI: 10.1111/j.1476-5381.1995.tb14950.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chlormethiazole on neuronal damage in a model of transient focal ischaemia

Abstract: 1 The effect of chlormethiazole has been studied in a transient middle cerebral artery (MCA) occlusion model of cerebral ischaemia in the rat. The MCA was occluded for 1 h by use of an intraluminal suture technique, with reperfusion for 24 h following removal of the occluding filament. Neuronal damage was determined by measurement of the area of necrosis following Cresyl Violet staining of sections taken through the ischaemic region. 2 In the initial experiment, occlusion of the MCA produced a large volume of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In global ischemia, its protective effect tended to disappear long-term and may have been mediated by hypothermia (Chaulk et al, 2003). Focal ischemia studies included a study of 1-h MCA suture occlusion in rats, followed by 24-h reperfusion, in which clomethiazole was given either 60 min prior to occlusion or at 10 min after the start of reperfusion (i.e., at 70 min after onset of ischemia) (Sydserff et al, 1995b). Histological protection was observed.…”
Section: Gaba Agonism: Clomethiazole Diazepammentioning
confidence: 99%
“…In global ischemia, its protective effect tended to disappear long-term and may have been mediated by hypothermia (Chaulk et al, 2003). Focal ischemia studies included a study of 1-h MCA suture occlusion in rats, followed by 24-h reperfusion, in which clomethiazole was given either 60 min prior to occlusion or at 10 min after the start of reperfusion (i.e., at 70 min after onset of ischemia) (Sydserff et al, 1995b). Histological protection was observed.…”
Section: Gaba Agonism: Clomethiazole Diazepammentioning
confidence: 99%
“…Clomethiazole has been shown to have neuroprotective effects in rat, gerbil, and marmoset models of cerebral ischaemia [6][7][8][9][10][11][12]. These findings suggested that clomethiazole might prevent neuronal degeneration following ischaemic stroke and the drug has undergone clinical development as a potential treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Ligation of the middle cerebral artery in rats for 60 min followed by a return to normal cerebral perfusion produces dramatic loss of cortical and striatal tissue on the side of the lesion (45). Following an i.p.…”
Section: Rodentsmentioning
confidence: 99%